MANAGEMENT OF THE DEVELOPMENT AND COMPETITIVE POSITIONS OF BUSINESS ENTITIES: MODELING THE INFLUENCE OF THE FACTORS OF THE INSTITUTIONAL ENVIRONMENT - PANCHENKO, Volodymyr (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The relevance of the issues of research in the field of identification and analysis of the influence of external environmental factors on entrepreneurial activity and the formation of competitive positions of business entities is substantiated. The purpose of the study is to provide a scientific basis for the theoretical and methodological aspects of managing the development and competitive positions of business entities and conducting econometric modeling of the influence of the factors of the institutional environment on the effectiveness of the tools of this direction of management. The factor load of the components of the index of economic freedom in Ukraine in 2000-2020 was estimated, which made it possible to determine the characteristic numbers of the correlation matrix for the components of the index of economic freedom in the country. The results of the assessment of the relationship between the turnover of small business entities per resident and the components of economic freedom in Ukraine are presented. The factor loading of the components of the indicator of the ease of conducting business activities of small business entities in Ukraine was calculated. Interrelationships between the volume of business activity and the components of the indicator of the quality of the business environment in Ukraine have been revealed. The scientific novelty of the research results lies in the improvement of the methodology for modeling the influence of external environmental factors on the development and strengthening of the competitive positions of business entities. The applied value of the obtained research results consists in establishing a complex of prerequisites that hinder the development and strengthening of the competitive positions of business entities in Ukraine, in particular in terms of the predominance of departmental interests over the interests of the country and the business sector, low effectiveness of regulatory legislation, limited responsibility of the authorities for obstacles to the functioning of sub business entities.